Rivalry and cooperation in the Asia-Pacific the dynamics of a region in transition - Beeson, Mark (World Scientific Co.Pte.Ltd., 2020)
"Provides a comprehensive and accessible introduction to the most important strategic and economic region in the world. Asia-Pacific is a region that is undergoing a major transformation, largely as a consequence of the rise of China and its growing rivalry with the United States. Whatever happens in the Asia-Pacific will profoundly influence global events, not just regional ones. Looking ahead, the region's future direction -- and even its name -- is contested and uncertain. This two-volume reference work, by one of the world's leading analysts of regional affairs, places these events in historical context and considers what they may mean for future political, economic and strategic relations. By focusing on the United States, China and the region's most significant middle powers, the book explains why and how the Asia-Pacific has become the fulcrum of international events."-- Provided by publisher